A Rumor has Spread like Wildfire? - Empirical Investigation of Information Propagation in Waiting Crowds - Lügering, Helena; Sieben, Anna (Collective Dynamics, 2024)
Information propagation in crowds tends to have a negative image. A common narrative is that information about a danger spreads like wildfire and leads to panic. In contrast, using person-to-person information sharing in crowd management as a complement to other communication channels has been discussed less. Even though previous research indicated that information does not propagate easily in crowds, more detailed research is lacking. In this study, two different experiments are presented to provide initial insights. In the main experiment, five groups of 33-41 participants took part in a total of 35 runs. In each run, a person in a waiting group was given a message or command that had to be passed on, whereby the knowledge about the task, the relevance of the message and the input side were varied. In the second experiment, this procedure was repeated with two larger groups of participants (n = 91 and n = 101). Overall, results showed that information propagated better when people were properly briefed on their task and have performed it several times. There was also a tendency for a higher density to foster faster propagation and for participants to rely on the spoken word rather than seeing a behavior performed. Yet, some participants did not receive the information at all or did not pass it on. In general, the direction of communication (e.g., back to front or left to right) was not always the same but information was usually passed along in a similar direction from where it came.